THE EFFECT OF HIGH INTENSITY INTERVAL TRAINING ON INCREASING ENDURANCE IN KARATE ATHLETES IN BONANG DEMAK - wijianto (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract Karate is a martial art that focuses on empty-handed combat, involving techniques like punches, kicks, and blocks. Endurance refers to the body's ability to supply oxygen to muscles during prolonged activity. High-Intensity Interval Training (HIIT) consists of short, intense exercise cycles (85%-95% of HR max) followed by rest periods of light activity. This study aims to examine the effect of HIIT on improving endurance in karate athletes in Bonang, Demak. Using a quasi-experimental method, the research applied a Pretest-Posttest with Control Group design to assess the impact on two groups. The study revealed that 65% of participants were male, and 70% were aged 15-19 years. A Non-Parametric Test was used to assess the effect of the intervention. The results showed a significant improvement in endurance before and after the intervention. After a 4-week program, the research demonstrated that HIIT positively influences endurance in karate athletes in Bonang, Demak.